Preparation, characterization and optimization of model propellant composites - Ng, Kennard Jun Hao (2019)
Composite propellants find application for rocket propulsion. A composite solid propellant consists of several chemical ingredients such as oxidiser, fuel, binder, plasticiser, curing agent and stabilizer. Heterogeneous solid propellants used in the rocket industry are usually composed of crystalline oxidiser particles, frequently ammonium perchlorate (AP), embedded in a polymeric binder (generally HTPB: Hydroxyl-Terminated Polybutadiene). Aluminum (Al) particles are also often added in order to improve propulsive performances. Composite propellants have a complex heterogenous microstructure. Evolution of the microstructure is determined by the interaction of the components of the formulation and the conditions adopted for processing the formulation. The effective structural and combustion properties of the combustion are the result of the microstructure and correlate it with properties for obtaining a composite propellant with optimal attributes. In this project, the effect of surface modification of aluminium fuel on the processability, microstructure and mechanical properties of a model composite propellant were investigated. The model composite propellant consisted of a inert simulant filler ammonium chloride (instead of AP), Al filler and HTPB binder cured with Toluene Diisocyanate (TDI) curing agent. The investigations were done as a function of two variables; a) coating percentage of surface modifier b) isocyanate to hydroxyl ratio or R-ratio used for curing the composite propellant. At first, gel time; referring to the time taken for a resin system to gel or become so highly viscous that it is no longer considered processable, was studied for HTPB/Al mixtures as a function of the surface modifier and R-ratio. Based on the gel time results, model propellant composites containing Al filler with 2.7% surface modifier were formulated and casted at two R-ratios of 0.9 and 1.0 . The microstructural characteristics of the model propellant composites were identified by using micro computer tomography (micro-CT) in order to understand the formation of porosity of samples. The mechanical properties of the composite specimens under compression were assessed. Based on the results, the process induced microstructure was correlated with the mechanical properties.